Spectroscopic characterization and mechanistic studies on visible light photoredox carbon–carbon bond formation by bis(arylimino)acenaphthene copper photosensitizers - Ng, Yik Yie (2018)
Currently, the most popular molecular photosensitizers used for synthetic organic chemistry and energy applications are still the noble metal-based ruthenium and iridium complexes that usually require expensive metal and ligand precursors. In contrast, bis(arylimino)acenaphthene (Ar-BIAN) are established redox non-innocent π-accepting ligands that are easily assembled in one condensation step from affordable and commercially available precursors. Herein, we have developed a series of Ar-BIAN Cu(I) complexes as visible light harvesting photosensitizers. Notably, one of these panchromatic, homoleptic Ar-BIAN Cu(I) complexes exhibits a radiative recombination lifetime that is longer than diffusion control, as observed by time-correlated single photon counting spectroscopy. The Ar-BIAN Cu(I) facilitates visible-light promoted atom transfer radical addition reactions via carbon-carbon bond formation with CBr3 radicals in good yields of up to 75%. Steady-state and transient absorption spectroscopic measurements, together with spectroelectrochemical experiments and intermediate isolation studies, were performed to obtain insights into this photoredox catalysis and provide guidelines for the general deployment of Ar-BIAN Cu(I) photosensitizers in synthetic organic chemistry and renewable energy applications.